The immune response to Mycobacterium avium induced in avian and human macrophage-like cell lines and in chickens - Shukur, Mohammed Shukri (2016)
Avian tuberculosis remains a significant economic problem for the poultry industry in many countries. An improved understanding of the interaction between host and mycobacteria is important in designing more efficient vaccine strategies. This study investigated the immune responses to M. avium (Ma.) strains isolated from different sources, Ma strains 1-2 isolated from chickens, Ma.3-5 from cattle and Ma.6-8 from humans, using human cells in vitro and avian cells in vitro and in vivo. The responses were characterised by expression levels of pro-inflammatory cytokines tumour necrosis factor alpha (TNF-α), interleukin (IL)-1β, IL-6 and chemokines CXCLi1 (K60) and CXCLi2 (IL-8) and nitric oxide production. A differential immune response was observed between the strains in terms of induction of cytokine and chemokine production in both human THP-1 and avian HD11 cells. With the exception of the avian strains 1 and 2, all strains induced increases in pro-inflammatory cytokines in THP1 cells. Two of the 3 bovine strains also had this effect in HD11 cells but the other strains had little effect. Use of specific inhibitors indicated that in THP-1 cells the extracellular regulating kinase (ERK) and c-Jun N-terminal kinase (JNK) pathways were important in inducing pro-inflammatory cytokines whereas the p38 pathway did not appear to be involved particularly in regulating TNF-α and IL-1β production. The results also indicate an interaction between the mitogen activated protein kinases (MAPK) pathways studied in regulation of cytokine production in HD11 cells. Although layer chickens were resistant to extensive M. avium multiplication in the tissues, significant expression of pro-inflammatory cytokines was observed in the liver of infected birds towards the end of the period of observation of 21 days as granulomata had started to appear, characterised by lymphocyte accumulation. In conclusion, the findings of this study provide further understanding of the host-mycobacteria interaction and that different strains of M. avium might behave differentially regardless of their source of isolation.